Analysis Of Earthquake Potential Energy in The Bali Subduction Zone - Pangastuti, Ni Putu Juliyant Ananda Rika; Suarbawa, Komang Ngurah; Putra, I Ketut; Purnami, Ni Luh Desi (BULETIN FISIKA, 2021)
Research has been carried out to analyze the potential energy of earthquakes in the subduction zone in the Bali region which aims to determine the seismicity index, a-value, b-value, return period and earthquake potential energy in the Bali region at coordinates 114.2º east longitude - 115.9º east longitude and 11 ,7º south latitude – 7.5º south latitude. Earthquake data used in the form of the date and time of the earthquake, earthquake coordinates in the form of latitude and longitude, earthquake depth and magnitude. The research was conducted using secondary data from the USGS (United State Geological Survey) earthquake catalog from 1970 to 2020 with a magnitude of 3-10. The data is modeled using Arc Gis software to obtain a seismicity map. The seismicity index, a-value, b-value, return period and earthquake potential energy were obtained using the least square method. Obtained a-value = 5.3 and b-value = -0.74, a seismicity index of 0.083 and an earthquake return period with a tested magnitude of M 0 of 6 M b of 12 years. The earthquake potential energy for this subduction zone is also obtained at 3,616×10 14 J .